Lithium ion battery diaphragm containing aminated boron nitride, preparation method of lithium ion battery diaphragm and lithium ion battery

By introducing aminated boron nitride into the lithium-ion battery separator, a separator with regular sponge-like pores and finger-like pores is prepared, which solves the problems of thermal shrinkage of polyolefin separators at high temperatures and the disordered growth of lithium dendrites, which significantly Improved safety and electrochemical performance of lithium-ion batteries.

CN119315211APending Publication Date: 2025-01-14SHENZHEN ACAD OF METROLOGY & QUALITY INSPECTION +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411281329.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing polyolefin lithium-ion battery separators are prone to heat shrinkage at high temperatures, the lithium dendrites on the anode surface have severe disordered growth, poor high-temperature cycle stability, large electrode polarization, conductivity, electrolyte wetting and flame retardant and electrochemical stability window is not ideal.

Method used

A lithium-ion battery separator containing aminated boron nitride is used. The preparation method includes providing an OPBI solution and a solution containing aminated boron nitride, and after mixing, coating on the substrate and removing the solvent to form a regular sponge-like pore and Diaphragms of finger-like holes.

Benefits of technology

The separator has excellent high temperature resistance, flame retardancy and electrochemical stability. It can effectively inhibit the disordered growth of lithium dendrites, improve the safety and electrochemical performance of lithium-ion batteries, and exhibit excellent discharge specific capacity and cycle performance. Stability and rate performance, especially excellent charge and discharge stability at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315211A_ABST
    Figure CN119315211A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a lithium ion battery diaphragm containing aminated boron nitride, a preparation method of the lithium ion battery diaphragm and a lithium ion battery, and the preparation method comprises the following steps: mixing an OPBI solution and an aminated boron nitride (f-BN) solution to obtain a mixed solution; coating a base material with the mixed solution, and removing the solvent in the mixed solution to obtain the lithium ion battery diaphragm containing aminated boron nitride, the lithium ion battery diaphragm containing aminated boron nitride is used for assembling a lithium ion battery. The aminated boron nitride is introduced into the battery diaphragm, the aminated boron nitride has good compatibility with the diaphragm substrate OPBI, uniform dispersion can be realized, the interface environment can be optimized, the microstructure of the diaphragm is uniform, and meanwhile, the battery diaphragm has a good application prospect. And the aminated boron nitride is utilized to change the diffusion force in the process of the non-solvent phase inversion method so as to obtain the high-temperature-resistant lithium ion battery diaphragm (OPBI (at) f-BN) which mainly comprises regular spongy pores and also comprises finger-shaped pores. The diaphragm electrolyte is good in wettability, high in conductivity and good in electrochemical stability, lithium ions can be induced to more quickly pass through the diaphragm and be uniformly deposited on the surface of a lithium metal anode through a unique pore structure, disordered growth of lithium dendrites is effectively inhibited, and the use safety and electrochemical performance of a lithium ion battery are improved. A battery assembled by using the diaphragm shows excellent specific discharge capacity, cycling stability and rate capability, and especially has excellent charge-discharge stability at a high temperature (90 DEG C); in addition, the electrode polarization degree of the battery is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery diaphragm containing amino boron nitride and a preparation method thereof, and a lithium ion battery. Background Art

[0002] The separator is one of the core components of lithium-ion batteries (LIBs). Its function is to separate the positive electrode from the negative electrode to prevent the battery from short-circuiting and causing safety accidents. At the same time, it ensures that lithium ions can pass through the microporous channels normally during charging and discharging to ensure the normal operation of the battery. The performance of the separator directly affects the safety, capacity, rate, life and other performance of the battery.

[0003] Polyolefin separators, such as polyethylene (PE) separators and polypropylene (PP) separators, are the mainstream products in the current separator market, and the production processes are mainly dry and wet. Due to the limitations of material properties and production processes, polyolefin separators still face several problems in the application process: First, the melting point of polyolefin materials is low, so polyolefin separators have poor heat resistance and are prone to thermal shrinkage at high temperatures, which leads to battery short circuits, and then causes dangerous events such as lithium battery fires and explosions; second, the conductivity, electrolyte wettability, flame retardancy, and electrochemical stability window of polyolefin separators are not ideal; third, the lithium dendrites of batteries assembled with polyolefin separators grow seriously during service, and lithium dendrites easily pierce the separator, causing micro-short circuits of lithium batteries, causing safety hazards to lithium batteries; fourth, the cycle stability of batteries assembled with polyolefin separators is very poor at high temperatures (such as 90°C); fifth, the polarization of battery electrodes assembled with polyolefin separators is relatively large.

[0004] In order to improve the safety and electrochemical performance of lithium batteries, some materials are coated on the surface of polyolefin diaphragms through different coating processes to form coated polyolefin diaphragms; the coated diaphragms on the market mainly include inorganic coated diaphragms, organic coated diaphragms, and organic + inorganic coated diaphragms. The coating materials used in this type of coated diaphragms usually have good heat resistance. However, the base material under the coating often shrinks at high temperatures, resulting in the collapse of the overall structure of the diaphragm. Therefore, this modification scheme based on polyolefin diaphragms cannot fundamentally solve the heat resistance problem of the diaphragm, and cannot fundamentally solve the safety of lithium batteries. In addition, coating also causes some negative effects, such as increased diaphragm thickness and increased body resistance (R b ) increases, the charge / discharge efficiency decreases, etc.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a lithium-ion battery separator containing amino boron nitride and a preparation method thereof, and a lithium-ion battery, aiming to solve the following problems: the existing polyolefin separators are prone to thermal shrinkage at high temperatures; the lithium dendrites on the anode surface of the lithium-ion battery assembled with the existing polyolefin separators have serious disordered growth; the lithium-ion battery assembled with the existing polyolefin separators has poor high-temperature cycle stability; the lithium-ion battery assembled with the existing polyolefin separators has large electrode polarization; the electrical conductivity, electrolyte wettability, flame retardancy, electrochemical stability window, etc. of the polyolefin separators are not ideal.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a lithium ion battery separator containing aminated boron nitride, comprising the steps of:

[0009] Providing an OPBI solution and a solution containing amino-bonded boron nitride;

[0010] The OPBI solution and the solution containing amino boron nitride are mixed to obtain a mixed solution;

[0011] The mixed solution is coated on a substrate, and the solvent in the mixed solution is removed to obtain a lithium ion battery separator containing amino boron nitride.

[0012] The method for preparing a lithium-ion battery separator containing amidated boron nitride, wherein the solvent of the solution containing amidated boron nitride and the solvent of the OPBI solution are jointly selected from one of N-methylpyrrolidone and dimethyl sulfoxide.

[0013] The method for preparing a lithium-ion battery separator containing aminated boron nitride, wherein the mass proportion of the aminated boron nitride in the mixed solution is 0.2%-0.8%.

[0014] The method for preparing a lithium-ion battery separator containing aminated boron nitride, wherein the aminated boron nitride is hexagonal boron nitride that is first ultrasonically treated with a NaOH solution and then aminated with γ-aminopropyltriethoxysilane (KH550).

[0015] The method for preparing a lithium-ion battery separator containing aminated boron nitride, wherein the solution containing aminated boron nitride is an aminated boron nitride solution with N-methylpyrrolidone as solvent; the solvent of the OPBI solution is N-methylpyrrolidone.

[0016] The method for preparing the lithium-ion battery separator containing amino boron nitride, wherein the mixing treatment is continuous stirring at room temperature for 15-24 hours.

[0017] The method for preparing the lithium-ion battery separator containing amino boron nitride, wherein the method for removing the solvent in the mixed solution is: placing the substrate coated with the mixed solution in anhydrous methanol for immersion treatment, and the immersion treatment is standing at room temperature for 8-15 minutes.

[0018] A lithium ion battery separator containing amino boron nitride is prepared by using the preparation method of the lithium ion battery separator (non-solvent phase transfer method).

[0019] The lithium-ion battery separator containing amino boron nitride has a thickness of 20-40 microns.

[0020] A lithium ion battery comprises a positive electrode sheet, a negative electrode sheet and a lithium ion battery separator containing amination boron nitride; the lithium ion battery separator containing amination boron nitride is located between the positive electrode sheet and the negative electrode sheet.

[0021] Beneficial effects: The present invention provides a lithium ion battery diaphragm containing aminated boron nitride and a preparation method thereof, and a lithium ion battery. The preparation method comprises the following steps: providing an OPBI solution and a solution containing aminated boron nitride; mixing the OPBI solution and the solution containing aminated boron nitride to obtain a mixed solution; coating the mixed solution on a substrate, and removing the solvent in the mixed solution to obtain a lithium ion battery diaphragm containing aminated boron nitride; and assembling a lithium ion battery using the lithium ion battery diaphragm containing aminated boron nitride. The present invention introduces aminated boron nitride into the battery diaphragm, and the aminated boron nitride has good compatibility with the diaphragm matrix OPBI, can achieve uniform dispersion and optimize the interface environment, and make the diaphragm microstructure uniform. At the same time, the aminated boron nitride is used to change the diffusion force in the non-solvent phase conversion process to obtain a high temperature resistant lithium ion battery diaphragm with regular sponge-like pores as the main body and finger-like pores. The membrane electrolyte has good wettability, high conductivity, and good electrochemical stability. The unique pore structure can induce lithium ions to pass through the membrane more quickly and deposit evenly on the surface of the lithium metal anode, effectively inhibiting the disordered growth of lithium dendrites and improving the safety and electrochemical performance of lithium-ion batteries. Batteries assembled using this membrane show excellent discharge specific capacity, cycle stability, and rate performance, especially excellent charge and discharge stability at high temperatures; in addition, the polarization degree of the battery electrode is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a schematic flow chart of a method for preparing a lithium-ion battery separator containing aminated boron nitride;

[0023] Figure 2 The structure diagram of γ-aminopropyltriethoxysilane (KH550) and the synthesis flow chart of f-BN;

[0024] Figure 3 The XPS spectra, EDS spectra and silicon element energy spectra of hydroxylated boron nitride and amino boron nitride;

[0025] Figure 4 SEM images of PP film, OPBI film, OPBI@BN composite film, and OPBI@f-BN composite film;

[0026] Figure 5 The results of heat resistance, flame retardancy, thermal weight loss curve, bending resistance, and electrolyte wettability of PP film, OPBI film, OPBI@BN composite film, and OPBI@f-BN composite film are shown in the figure;

[0027] Figure 6 The electrochemical performance data of PP film, OPBI film, OPBI@BN composite film, and OPBI@f-BN composite film are shown in Figure 2.

[0028] Figure 7 The potential variation diagram of symmetric batteries Li / PP / Li and Li / OPBI@f-BN / Li in long cycles;

[0029] Figure 8 It is the battery cycle stability test result diagram and the charge and discharge platform curve diagram;

[0030] Fig. 9 This is the rate performance data diagram of LiFePO4 / Li half-cell;

[0031] Fig.10 Cyclic discharge performance of LiFePO4 / Li battery assembled with PP membrane and OPBI@f-BN composite membrane at 90℃. DETAILED DESCRIPTION

[0032] The present invention provides a lithium ion battery separator containing amino boron nitride and a preparation method thereof, and a lithium ion battery. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.

[0034] like Figure 1As shown, the present invention provides a method for preparing a lithium ion battery separator containing amino boron nitride and a lithium ion battery, comprising the steps of:

[0035] Step S10: providing an OPBI solution and a solution containing amino-bonded boron nitride;

[0036] Step S20: mixing the OPBI solution and the solution containing amino boron nitride to obtain a mixed solution;

[0037] Step S30: coating the mixed solution on a substrate, and removing the solvent in the mixed solution to obtain a lithium ion battery separator containing amino boron nitride;

[0038] Step S40: Assembling a lithium-ion battery using the lithium-ion battery separator containing amino boron nitride.

[0039] In the present embodiment, polybenzimidazole (OPBI) is a polymer with excellent thermal stability and mechanical properties. Since the OPBI molecular chain contains polar ether bonds, it can enhance the affinity with the electrolyte. Therefore, it is prepared into a polymer diaphragm and applied to lithium-ion batteries, which can improve the safety and electrochemical performance of the battery. h-BN has the advantages of high melting point, large specific surface area and good stability, and can be used as one of the good choices for polymer doping materials. However, due to the surface inertness of h-BN, it is poorly compatible with polymers. Therefore, it is necessary to surface modify h-BN to improve its dispersibility and compatibility in polymers. Amino groups have polar effects, which can reduce surface tension and increase permeability. Introducing amino groups can not only adjust its compatibility with polymers, but also enhance the interaction between the diaphragm and the electrolyte, making it easier for the electrolyte to penetrate into the inside of the diaphragm, thereby improving the electrolyte absorption rate and liquid retention capacity of the diaphragm, thereby improving battery performance. At the same time, considering that the boron atom of h-BN still has empty orbital characteristics after forming a covalent bond, it presents an electrophilic structure and is easy to form a chemical bond with -OH containing a lone pair of electrons. The triethoxy group in γ-aminopropyltriethoxysilane (KH550) is easily hydrolyzed to form trisilanol, which can react with the hydroxyl group grafted on the surface of h-BN to achieve the grafting of amino molecules. The composite membrane of amino boron nitride and OPBI was prepared by the non-solvent induced phase separation (NIPS) process.

[0040] Specifically, considering the characteristics of polybenzimidazole and amino boron nitride, the two are composited into a lithium-ion battery separator and applied to lithium-ion batteries, which helps to solve the safety problems of lithium-ion batteries caused by the heat resistance, flammability and disordered growth of lithium dendrites of the separator. At the same time, from the perspective of the separator, the electrochemical properties of lithium-ion batteries such as rate and cycle stability (including room temperature and high temperature) are improved, and the polarization of battery electrodes is reduced. Experimental data show that compared with commercial polyolefin separators, the lithium-ion battery composite separator prepared by the non-solvent phase separation process has excellent heat resistance, flame retardancy and the effect of inhibiting the disordered growth of lithium dendrites, which can effectively improve the safety of lithium-ion batteries. At the same time, the lithium-ion battery separator exhibits higher ionic conductivity (1.29mS cm -1 ) and electrolyte absorption rate (493.4%). The peak discharge capacity of the LiFePO4 / Li battery assembled with the lithium-ion battery separator at 0.5C is 153.98 mAh g -1 After 200 cycles, the capacity retention rate of the battery is 93.3%. In addition, the LiFePO4 / Li battery assembled with the lithium-ion battery separator can also operate at a temperature of 90° C. and has a considerable capacity retention rate.

[0041] In some embodiments, the solvent of the solution containing amination boron nitride and the solvent of the OPBI solution are jointly selected from but not limited to one of N-methylpyrrolidone (NMP) and dimethyl sulfoxide (DMSO); ensuring that the solvents of the solution containing amination boron nitride and the OPBI solution are consistent facilitates the subsequent use of a non-solvent induced separation process.

[0042] In some embodiments, in the mixed solution, the mass proportion of the amino boron nitride is 0.2%-0.8%; the lithium-ion battery separator can contain an appropriate amount of amino boron nitride, so that the amino boron nitride can be used to improve the diffusion force during the non-solvent phase transformation method to obtain a high-temperature resistant lithium-ion battery separator (OPBI@f-BN) with mainly regular sponge-like pores and finger-like pores.

[0043] In a preferred embodiment, in the mixed solution, the ratio of the mass of OPBI to the volume of the solvent of the mixed solution is 1 g:(9-11) ml, but is not limited thereto; specifically, it can also be 1 g:10 ml.

[0044] In a preferred embodiment, the amination boron nitride is a product of hexagonal boron nitride being first hydroxylated and then amination; the solution containing amination boron nitride is an amination boron nitride solution with N-methylpyrrolidone as solvent; the solvent of the OPBI solution is N-methylpyrrolidone; since polybenzimidazole has excellent thermal stability, mechanical properties, flame retardancy, etc., amination boron nitride has excellent thermal stability, large specific surface area, good stability, etc., and since amination boron nitride has polar groups such as -NH on its surface, it has good interfacial compatibility with polybenzimidazole; therefore, in view of the material characteristics of polybenzimidazole and amination boron nitride, the two are composited to prepare a diaphragm for use in lithium-ion batteries, which helps to solve the safety problems of lithium-ion batteries caused by the heat resistance, flammability and disordered growth of lithium dendrites of the diaphragm, and at the same time improve the electrochemical properties of lithium-ion batteries such as rate and cycle stability (including room temperature and high temperature) from the perspective of the diaphragm, and reduce the polarization of battery electrodes.

[0045] In some embodiments, the mixing treatment is continuous stirring at room temperature for 15-24 hours; stirring at room temperature for 15-24 hours allows OPBI and amino boron nitride to be evenly mixed, in preparation for preparing a lithium-ion battery separator with better performance.

[0046] In some embodiments, in step S30, the method for removing the solvent in the mixed solution is: placing the substrate coated with the mixed solution in anhydrous methanol for immersion treatment, the immersion treatment is standing at room temperature for 8-15 minutes, and preparing the lithium ion battery separator using a non-solvent induced phase separation process. Since OPBI is insoluble in methanol, amino boron nitride is also insoluble in methanol at room temperature, and NMP or DMSO is soluble in methanol, the substrate coated with the mixed solution is allowed to stand at room temperature for 8-15 minutes, and methanol is used to make the mixed solution quickly form a film, and replace NMP or DMSO to form pores, so that the prepared lithium ion battery separator has a microscopic pore structure with regular sponge-like pores as the main body and finger-like pores, which is conducive to the uniform deposition of lithium ions on the anode surface, thereby inhibiting the disordered growth of lithium dendrites and improving the safety of the battery during service.

[0047] In some embodiments, in step S30, after the soaking treatment, a drying treatment is further performed to remove methanol in the pores.

[0048] In some embodiments, the substrate is, but is not limited to, a glass plate.

[0049] In addition, the present invention also provides two lithium-ion battery separators, which are prepared by using the preparation method of the lithium-ion battery separator containing amino boron nitride.

[0050] In this embodiment, amino boron nitride is introduced into the lithium-ion battery separator, and the amino boron nitride is used to improve the diffusion force during the non-solvent phase conversion method to obtain a high-temperature resistant lithium-ion battery separator (OPBI@f-BN) with regular sponge-like pores and finger-like pores. The lithium-ion battery separator has excellent thermal stability and excellent flame retardancy, no thermal shrinkage occurs at 200°C, and no obvious combustion phenomenon occurs when placed on a flame; the lithium-ion battery separator has good electrolyte wettability, a large electrolyte absorption rate (493.4%), and high conductivity (1.29mS cm -1 ), good electrochemical stability; the lithium-ion battery separator has a unique microscopic pore structure with regular sponge-like pores as the main part and finger-like pores, which can induce lithium ions to pass through the separator more quickly and deposit evenly on the surface of the lithium metal anode, effectively inhibit the disordered growth of lithium dendrites, and improve the safety and electrochemical performance of lithium-ion batteries. The battery assembled with the separator exhibits excellent discharge specific capacity, cycle stability, and rate performance, especially excellent charge and discharge stability at high temperature; in addition, the polarization degree of the battery electrode is low.

[0051] In some embodiments, the lithium ion battery separator containing amino boron nitride has a thickness of 20-40 microns; the lithium ion battery separator at this thickness has excellent thermal stability and can inhibit the disordered growth of lithium dendrites.

[0052] In addition, the present invention also provides a lithium-ion battery, including a positive electrode, a negative electrode and a lithium-ion battery separator containing amidated boron nitride; the lithium-ion battery separator containing amidated boron nitride is located between the positive electrode and the negative electrode.

[0053] In this embodiment, the LiFePO4 / Li battery assembled with the lithium ion battery separator containing amino boron nitride has a peak discharge capacity of 153.98 mAh g at 0.5C. -1 After 200 cycles, the capacity retention rate of the battery is 93.3%. Moreover, the LiFePO4 / Li battery assembled with the lithium-ion battery separator containing aminated boron nitride can also operate at a temperature of 90°C and has a considerable capacity retention rate; and the battery assembled with the lithium-ion battery separator containing aminated boron nitride can operate smoothly and safely at high temperatures (such as 90°C).

[0054] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.

[0055] Example 1

[0056] This embodiment provides a method for preparing a lithium-ion battery separator containing amino boron nitride (OPBI@f-BN composite membrane) and a lithium-ion battery. The schematic diagram of the process is shown in FIG. Figure 1 As shown, the steps include:

[0057] Step S1: dissolving OPBI in NMP to form a uniform OPBI solution;

[0058] The aminated boron nitride (f-BN) is dissolved in NMP to form an aminated boron nitride (f-BN) solution (aminated boron nitride accounts for 20 mg / ml) with NMP as solvent, that is, an aminated boron nitride solution.

[0059] Step S2: adding the amination boron nitride solution to the OPBI solution, and continuously stirring at room temperature for 20 hours to obtain a mixed solution, wherein the ratio of OBPI:NMP in the mixed solution is 1 g:10 ml.

[0060] Step S3: The obtained mixed solution was coated on a glass plate with a scraper and transferred into anhydrous methanol (MeOH) for 10 min to obtain a porous film, and then the porous film was dried at room temperature to obtain an OPBI@f-BN composite film.

[0061] Step S4: assembling a lithium-ion battery using the lithium-ion battery separator containing amino boron nitride.

[0062] The schematic diagram of the preparation process of f-BN is shown in Figure 2 As shown in Figure 1, the process is divided into two steps. The first step is the hydroxylation of h-BN: at 30 °C, 1 g of NaOH was dissolved in 40 mL of distilled water to prepare a saturated NaOH solution. Subsequently, 1 g of h-BN solid, and then the composite was ultrasonically treated for 1 hour. After repeating this process 3 times, the composite solid particles were washed with deionized water until neutral. Finally, the composite was dried at 80°C for 72 hours to obtain hydroxylated boron nitride (b-BN) solid particles; the second step is the amination treatment of b-BN: 0.04g of b-BN was added to a 1:1 composite solution of ethanol and KH550, and ultrasonically treated for 12 hours. During the process, (OC2H5)3 in the KH550 molecule was hydrolyzed to form trisilanol, which then reacted with the hydroxyl groups on the surface of b-BN, so that the KH550 molecules were successfully grafted on BN to obtain amination boron nitride (f-BN). The final product was separated by centrifugation and washed three times with deionized water, and then the excess KH550 was removed by Soxhlet extraction and dried at 80°C for 24 hours.

[0063] For comparison, this embodiment also provides PP (polypropylene) film, OPBI film, and OPBI@BN, wherein the preparation methods of OPBI film and OPBI@BN are the same as the preparation method of OPBI@f-BN composite film, both of which adopt a non-solvent phase transfer method.

[0064] The chemical composition of b-BN and f-BN materials is characterized as follows:

[0065] Figure 3 The XPS spectrum of b-BN, the wide XPS spectrum of f-BN, the EDS total spectrum of f-BN, and the EDS energy spectrum of Si element in f-BN. Combining the results of XPS analysis and EDS element analysis, it can be concluded that the modified f-BN material was successfully prepared in this experiment.

[0066] The performance tests of PP film, OPBI film, OPBI@BN composite film and OPBI@f-BN composite film are as follows:

[0067] Figure 4 SEM images of PP film, OPBI film, OPBI@BN composite film, and OPBI@f-BN composite film; Figure 4 It can be seen that compared with the PP diaphragm, the pores on the upper and lower surfaces of the OPBI, OPBI@BN and OPBI@f-BN diaphragms are larger and more regular in shape; in addition, Figure 4 It can also be seen that compared with OPBI and OPBI@BN membranes, the pore arrangement on the surface of OPBI@f-BN membrane is more dense and uniform. From the cross-sectional view, it can be seen that the OPBI@f-BN membrane has a microstructure pore channel with regular sponge-like pores and finger-like pores. The main reason is that the addition of f-BN changes the direction and magnitude of the diffusion force in the NIPS process and changes the process of material diffusion. This pore structure is conducive to the uniform deposition of lithium ions on the anode surface, thereby inhibiting the disordered growth of lithium dendrites and improving the safety of the battery during service.

[0068] Figure 5 The results are the high temperature resistance, flame retardancy, thermal degradation resistance, bending resistance and electrolyte wettability of PP film, OPBI film, OPBI@BN composite film and OPBI@f-BN composite film. Figure 5 (a) The PP diaphragm showed no obvious dimensional changes at 100°C; however, it shrank significantly at 150°C and melted at 200°C. In contrast, the three diaphragms based on OPBI showed no obvious dimensional changes after being tested at 200°C for 1h, showing good dimensional stability. Figure 5(b) It can be seen that the PP diaphragm shrinks rapidly when in contact with flames and burns quickly when in contact with flames. In contrast, the OPBI diaphragm does not burn when in contact with flames, but instead forms black carbides and releases smoke. This phenomenon is attributed to the high carbon content and low volatility of the OPBI diaphragm, and the carbonized layer formed can effectively protect itself. OPBI@f-BN with the addition of f-BN also does not undergo a combustion reaction when in contact with flames. In addition to the flame retardancy of OPBI itself, hexagonal boron nitride itself also has a high melting point and good thermal stability, making the diaphragm not easily heated and induced to burn. Figure 5 (c) shows that the PP membrane starts to lose weight at around 350°C; when the temperature reaches around 480°C, the weight retention rate of the PP membrane is almost 0, indicating that the PP membrane is completely burned. In contrast, the starting weight loss temperature of the OPBI and OPBI@f-BN membranes is about 540°C, and they have a higher weight retention rate at 600°C. It is worth noting that due to the addition of f-BN, the weight retention rate of the OPBI@f-BN membrane is slightly higher than that of the OPBI membrane at 600°C. Figure 5 (d) shows that after bending, folding and other treatments, the OPBI@f-BN membrane was not found to be cracked or damaged. Figure 5 (e) shows that the electrolyte contact angle of the OPBI@f-BN composite film is the smallest, indicating that its electrolyte wettability is the best.

[0069] Figure 6 The electrochemical performance test diagrams of PP film, OPBI film, OPBI@BN composite film, and OPBI@f-BN composite film. Figure 6 (a) and (b) show that the conductivity of OPBI@f-BN composite membrane is the highest, reaching 1.29 mS cm -1 . Figure 6 (c) shows that the interfacial resistance of the battery assembled with OPBI@f-BN membrane is the smallest. Figure 6 The results of (a) and (b) are consistent. Figure 6 (d) shows that the OPBI@f-BN separator exhibits an electrochemical stability window as high as 5.15 V, with excellent electrochemical stability.

[0070] Figure 7 The potential changes of symmetric cells Li / PP / Li and Li / OPBI@f-BN / Li assembled with PP membrane and OPBI@f-BN composite membrane in long-term cycling. In the 1640-hour long cycle, the current density is 0.5 mA cm -2 When the Li / PP / Li half-cell was prepared, a high overpotential of 0.03 V was generated at the onset of dissociation or deposition, which indicated that the assembled half-cell had high polarization and poor lithium plating / stripping performance.+ The Li / OPBI@f-BN / Li half-cell has a relatively low overpotential of about 0.001 V due to its high conductivity and low lithium interface resistance. At the same time, the Li / OPBI@f-BN / Li half-cell assembled with the composite separator can maintain long-term stability and extremely low polarization voltage during a cycle of up to 3000 h. This further proves that the OPBI@f-BN separator has an effective effect on inhibiting the random growth of lithium dendrites.

[0071] Figure 8 The charge and discharge cycle performance and charge and discharge platform curves of batteries assembled with PP film, OPBI film, OPBI@BN composite film, and OPBI@f-BN composite film, respectively. Figure 8 (a) shows that the initial discharge capacity of the LFP / Li half-cell assembled with PP separator is 128.3 mAh g -1 , the peak capacity is 136.22 mAh g -1 The initial discharge capacity of the half-cells assembled with OPBI, OPBI@BN and OPBI@f-BN membranes was 132.02 mAh g -1 、140.61mAh g -1 and 139.05mAh g -1 , and the peak capacities are 135.76 mAh g -1 , 146.47mAh g -1 and 153.98mAh g -1 In addition, the capacity retention rate of the LFP / Li half-cell assembled with the OPBI@f-BN membrane can reach 93.3%, which is higher than the 74.1% of the PP membrane. The battery assembled with the OPBI@f-BN composite membrane exhibits the best charge and discharge cycle performance. Figure 8 (b) and (c) show that the high and low voltage potential difference of the battery assembled with OPBI@f-BN membrane is relatively small during the charging and discharging process. This phenomenon also shows that during the operation of the battery, the electrode polarization is low and the battery has more stable electrochemical performance. This phenomenon occurs due to the high porosity and high conductivity of the OPBI@f-BN membrane, which promotes the rapid transmission of lithium ions, effectively reduces the internal resistance, and reduces the polarization of the electrode.

[0072] Fig. 9 The rate cycling performance of the battery assembled with PP membrane, OPBI membrane and OPBI@f-BN composite membrane. The battery assembled with OPBI@f-BN separator exhibits a high discharge capacity at all different charge and discharge currents, especially at a high rate of 2C, with a discharge capacity of up to 130.51 mAh g -1, showing excellent fast charge and discharge performance. This is mainly due to the advantages of OPBI@f-BN separator, such as high ionic conductivity, good electrolyte affinity and stability with lithium interface, which help to reduce internal polarization of the battery and improve charge transfer efficiency.

[0073] Fig.10 The test data of the battery assembled with PP film and OPBI@f-BN composite film was cycled at a rate of 0.5C at 90°C. After 50 cycle tests, the capacity of the battery assembled with OPBI@f-BN membrane remained relatively stable without obvious attenuation, while the capacity of the battery assembled with PP membrane decreased significantly. This result shows that the battery assembled with OPBI@f-BN membrane has better cycle stability in high temperature environment. The test results prove that OPBI@f-BN membrane not only ensures the safe operation of the battery at room temperature, but also supports the battery to show excellent working performance in high temperature environment.

[0074] In summary, the present invention provides a lithium ion battery diaphragm containing aminated boron nitride and a preparation method thereof, and a lithium ion battery, wherein the preparation method comprises the steps of: providing an OPBI solution and a solution containing aminated boron nitride; mixing the OPBI solution and the solution containing aminated boron nitride to obtain a mixed solution; coating the mixed solution on a substrate, and removing the solvent in the mixed solution to obtain a lithium ion battery diaphragm containing aminated boron nitride; and assembling a lithium ion battery using the lithium ion battery diaphragm containing aminated boron nitride. The present invention introduces aminated boron nitride into the battery diaphragm, and the aminated boron nitride has good compatibility with the diaphragm matrix OPBI, which can achieve uniform dispersion and optimize the interface environment, so that the microstructure of the diaphragm is uniform. At the same time, the aminated boron nitride is used to improve the diffusion force in the non-solvent phase conversion process, thereby obtaining a high temperature resistant lithium ion battery diaphragm (OPBI@f-BN) with regular sponge-like pores as the main body and finger-like pores. The membrane electrolyte has good wettability, high conductivity, and good electrochemical stability. The unique pore structure can induce lithium ions to pass through the membrane more quickly and deposit evenly on the surface of the lithium metal anode, effectively inhibiting the disordered growth of lithium dendrites and improving the safety and electrochemical performance of lithium-ion batteries. Batteries assembled using this membrane show excellent discharge specific capacity, cycle stability, and rate performance, especially excellent charge and discharge stability at high temperatures; in addition, the polarization degree of the battery electrode is low.

[0075] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a lithium ion battery separator containing amino boron nitride, characterized in that: Includes steps: providing an OPBI solution and an amination boron nitride solution; The OPBI solution and the amination boron nitride solution are mixed to obtain a mixed solution; The mixed solution is coated on a substrate, and the solvent in the mixed solution is removed to obtain a lithium ion battery separator containing amino boron nitride.

2. The method for preparing a lithium ion battery separator containing aminated boron nitride according to claim 1, characterized in that: The solvent of the amination boron nitride solution and the solvent of the OPBI solution are both selected from one of N-methylpyrrolidone and dimethyl sulfoxide.

3. The method for preparing a lithium ion battery separator containing aminated boron nitride according to claim 1, characterized in that: In the mixed solution, the mass proportion of the amino boron nitride is 0.2%-0.8%.

4. The method for preparing a lithium ion battery separator containing aminated boron nitride according to claim 1, characterized in that: In the preparation process of the amination boron nitride, hexagonal boron nitride (BN) is first subjected to hydroxylation treatment and then to amination treatment.

5. The method for preparing a lithium ion battery separator containing aminated boron nitride according to claim 4, characterized in that: The amination of boron nitride is firstly treated with an ultrasonic solution of NaOH and then γ - Hexagonal boron nitride after amination with aminopropyltriethoxysilane (KH550).

6. The method for preparing a lithium ion battery separator containing aminated boron nitride according to claim 1, characterized in that: The mixing process is to continue stirring at room temperature for 15-24 hours.

7. The method for preparing a lithium ion battery separator containing aminated boron nitride according to claim 1, characterized in that: The method for removing the solvent in the mixed solution is: placing the substrate coated with the mixed solution in anhydrous methanol for immersion treatment, and the immersion treatment is standing at room temperature for 8-15 minutes.

8. A lithium ion battery separator containing amino boron nitride, characterized in that: The lithium ion battery diaphragm containing amino boron nitride is prepared by the preparation method of any one of claims 1 to 7, and the microscopic pore structure of the diaphragm is mainly regular sponge-like pores with finger-like pores.

9. The lithium ion battery separator containing amino boron nitride according to claim 8, characterized in that: The thickness of the lithium ion battery separator containing amino boron nitride is 20-40 microns.

10. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and a lithium-ion battery separator containing amidated boron nitride as described in any one of claims 8 to 9; the lithium-ion battery separator containing amidated boron nitride is located between the positive electrode sheet and the negative electrode sheet.